The Role of Fintech in the Transformation of the Cashless Society of the Sharia Financial Sector with A Literature Review Approach - Wiyani, Sri; Muhammad Syahbudi; Aqwa Naser Daulay (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2025)
The development of financial technology (fintech) has driven a significant transformation in the Islamic finance sector, particularly toward a cashless society, where transactions are conducted without cash. This study aims to analyze the role of fintech in this transformation through a literature review and bibliometric analysis using data from 21 Scopus journals, 26 from Google Scholar, and 15 from Crossref. Of the 62 journals analyzed, approximately 70% indicate that fintech plays a significant role in increasing financial inclusion, operational efficiency, and the development of Sharia-compliant financial products. Innovations such as digital payments, peer-to-peer lending, and Sharia-compliant investments are key drivers of this transition. Analysis using Vosviewer also reveals the dominance of the keyword "fintech," which is closely correlated with Islamic banking, although specific studies related to a cashless society are still limited. However, challenges such as regulation, data security, and public literacy remain obstacles that need to be overcome. Overall, fintech is a key catalyst in the digitalization of inclusive and sustainable Islamic finance.